Seroprevalence of Toxoplasmosis Antibodies among Diabetes Mellitus Patients and Assessment some Biochemical Markers - Saeed, Sarah Ali; Al-Aubaidi, Israa Kasim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Toxoplasma gondii is an protozoan intracellular coccidian protozoan parasite. Latent toxoplasmosis threat to immunocompetent individuals. Diabetic patients are more susceptible to infect with toxoplasmosis due to their low level of immunity response. The purpose of this research is to define the association between toxoplasmosis and diabetes mellitus and detection serum levels of chemokines (monocyte chemoattractant protien-1 and transforming growth factor-β) in diabetic patients infected with toxoplasmosis. Serum samples were collected from 120 diabetic patients and 50 healthy individuals as a control group from the Imamein Kadhimein Medical City in Baghdad. In order to diagnose diabetes, fasting and random blood glucose tests were used . The diagnosis of toxoplasmosis was done by using toxo IgM and IgG immulite torch assay. Chemokines levels were measured by ELISA method. The results clarified that all samples were seronegative for IgM antibodies while 50 (41.67%) diabetic patients were seropositive for IgG antibodies and 70 (58.33%) diabetic patients and 50 healthy controls were seronegative for IgG antibodies. Serum level of MCP-1 was recorded an increase in a group of diabetic patients infected with toxoplasmosis 169.66 ± 131.35 pg/ml with highly significant differences (P < 0.001) also TGF-β level was increased in a group of diabetic patients infected with toxoplasmosis 0.53 ± 0.242 pg/ml with highly significant differences (P ≤ 0.0001) when compare with the studied groups.